Psychosocial and Health System Factors in Disclosure of HIV Status to Children Living with HIV in Malawi: A Formative Evaluation of a Disclosure Resource - Kalembo, Fatch Welcome (Curtin University, 2017)
This study aimed to evaluate the current practice of HIV disclosure to Malawian children and to assess the need and acceptability of a series of age-appropriate story books intended to help with the disclosure process. A mixed methods approach was used to collect data from 700 adults caring for children living with HIV. The prevalence of non-disclosure of HIV was 64%, and 98% of participants supported the idea of developing the proposed story books.